Nano calcium carbonate with high specific surface area, high dispersion and high purity and preparation method thereof

By adding ammonium salts or ammonia water that are easily decomposed by heat and controlling the carbonization conditions, the problem of difficulty in improving the specific surface area, dispersion and purity of nano-calcium carbonate is successfully solved, and efficient and economical preparation of nano-calcium carbonate is achieved.

CN119551700APending Publication Date: 2025-03-04GUANGXI HUANA NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411622529.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the specific surface area, dispersion and purity of nano calcium carbonate, and the frequent use of a large number of additives leads to a decrease in purity.

Method used

After calcining limestone, digestion with water, adding ammonium salts or ammonia water that are easily decomposed by heat to promote the dissolution of magnesium, and controlling the temperature and stirring rate during the carbonization process, gradually adding water to dilute, inhibiting recrystallization, and finally removing magnesium ions through overcarburization, obtaining nano-calcium carbonate with high specific surface area, high dispersion and high purity.

Benefits of technology

The high specific surface area, high dispersion and high purity of nano calcium carbonate are achieved, which reduces production costs, simplifies the process flow, and enhances the application value of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551700A_ABST
    Figure CN119551700A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-specific-surface-area, high-dispersion and high-purity nano calcium carbonate, which comprises the following steps: S1, calcining limestone, digesting the lime and water in proportion, and screening to remove gravel; s2, ammonium salt or ammonia water is added into the obtained lime slurry, and the solid content is adjusted; s3, layering the lime slurry after standing, and then concentrating to obtain concentrated lime slurry; s4, putting the concentrated lime slurry into a carbonization tower, and carrying out carbonization reaction by controlling the temperature, the stirring rate, the carbon dioxide concentration and the carbon dioxide flow; s5, when over-carbonization is achieved, obtaining a nano calcium carbonate suspension; s6, standing and settling the suspension, and removing upper-layer water to enable the solid content to be within a certain range; and S7, adding stearic acid into the suspension liquid for surface modification, and carrying out filter pressing, drying, crushing and sieving on the obtained suspension liquid to obtain the nano calcium carbonate powder. The method is low in raw material cost, economical, environmentally friendly, simple in control step, short in carbonization time, high in production efficiency and convenient for industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic material preparation, and relates to high specific surface area, high dispersion, high purity nano calcium carbonate and a preparation method thereof. Background Art

[0002] Nano calcium carbonate is a white, non-toxic inorganic powder with the small size effect of nano materials. It is often used as a filler or additive in plastics, adhesives, coatings, paints, rubber, cosmetics, etc.

[0003] The preparation process of nano calcium carbonate in China is mainly based on bubbling carbonization, using CO2 to precipitate and crystallize in a Ca(OH)2 suspension to obtain nano-scale fine particles. Research on nano calcium carbonate is mainly aimed at performance optimization, such as particle fineness, dispersibility, product purity, etc. There is no unified understanding of the mechanism of bubbling carbonation of nano calcium carbonate. Precipitated calcium carbonate (including nano calcium carbonate) follows the non-classical nucleation theory. According to the research results of Hiroaki Imai of Shiraishi Industries, Ltd. in Japan, the crystal formation of nano calcium carbonate exists in the form of linear bodies at the beginning of carbonization. As the reaction proceeds, the linear bodies gradually grow and become coarser, accompanied by clusters. At the end of the reaction, the linear bodies break down to form nanoparticles. This is similar to our research findings. According to our research, the basic rule of the bubbling carbonation method for preparing nano calcium carbonate is that the ore is calcined to form lime, which contains calcium oxide, magnesium oxide, silicon oxide, iron oxide, aluminum oxide and other impurities. After the lime is digested in water, fine calcium hydroxide and magnesium hydroxide are formed. Silicon, aluminum, and iron are mostly stable during calcination and mixed in sand and gravel. Screening and refining can remove most of the silicon, aluminum, iron and other impurities. However, magnesium will gradually form hydroxides during the digestion process, just like calcium, accompanying the entire process of suspension carbonation. During the carbonation process, the calcium hydroxide suspension gradually forms linear bodies, which gradually grow and eventually break and decompose into cubic nanoparticles at the end of carbonation. At the end of carbonation, after the calcium in the system reacts completely to become calcium carbonate, magnesium hydroxide participates in the reaction to form magnesium carbonate. If it is further overcarbonized, magnesium carbonate will form easily soluble magnesium bicarbonate. Yuki Kezuka of Shiraishi Industries Co., Ltd. also studied the role of Mg in the formation process of nano calcium carbonate. They believe that Mg continuously adheres to the surface during the formation stage of the linear body, inhibiting the breakage of the nano chain and making it difficult to form evenly dispersed nanoparticles. The presence of magnesium is the key to the difficulty of nano calcium carbonate to form dispersed particles. It is also an impurity element that reduces the purity of nano calcium carbonate and may be doped in calcium carbonate crystal particles. However, we do not agree with the understanding of the existence form of magnesium. During the carbonation process, the distribution of magnesium in the liquid phase is extremely low, and it is only released in large quantities after carbonization, which further shows that magnesium is not as the result of Shiraishi Industries Co., Ltd.'s research. Chinese patents CN 202410653167, a method for treating dolomite, and CN202410603306, a method for separating calcium and magnesium based on the carbonization stage, magnesium oxide and preparation method, use dolomite carbonization to achieve calcium and magnesium separation, which utilizes the method of dissolving magnesium in the liquid phase for easy separation by carbonization. The process from calcination to the end of carbonation of nano calcium carbonate has the following chemical reactions:

[0004] (1)CaMg(CO3)2—>CaO+MgO+2CO2↑

[0005] (2)CaO+H2O-Ca(OH)2↓

[0006] (3)Mgo+H2O-Mg(OH)2↓

[0007] (4)Ca(OH)2+CO2-CaCO3↓+H2O

[0008] (5)Mg(OH)2+CO2+H2O-Mg(HCO3)2

[0009] Reaction (5) occurs vigorously after reaction (4) is completed, and the Mg(HCO3)2 formed is easily soluble.

[0010] Regarding the purity of precipitated calcium carbonate, in the research of precipitated calcium carbonate, most of them are based on low concentration of Ca(OH)2 (saturated solution or lower), with sodium carbonate or sodium bicarbonate as carbon source, and crystallized to form calcium carbonate. The purity of calcium carbonate obtained by these methods is relatively low, because the presence of sodium ions is attached to the surface of calcium carbonate, and it is difficult to improve the purity by separation and impurity removal. Compared with the double decomposition method and causticization method, the use of bubbling carbonation and gas stripping with carbon dioxide as the carbon source, the introduction of other impurity elements, is an effective method to ensure the purity of nano calcium carbonate. The purity improvement of nano calcium carbonate preparation process belongs to physical methods in the lime slurry refining stage, while in the final stage, magnesium enters the liquid phase after overcarbonization, which belongs to chemical methods. Inorganic Salt Industry Volume 37, Issue 2, Baiyunshan, Liu Taihong, and Liu Zhen mentioned that ammonium salts can increase the leaching rate of magnesium oxide. In order to further promote the dissolution of magnesium, appropriate ammonium salts can be added in the digestion stage to make magnesium more soluble and increase the leaching rate of magnesium ions, while calcium ions have little effect. In addition, ammonium has an impact on the purity of nano calcium carbonate, but ammonium salts are easy to decompose. Subsequent drying can decompose ammonium salts and improve purity.

[0011] For the specific surface area of ​​nano calcium carbonate, the initial stage of carbonization is particularly important because its crystallization process follows non-classical nucleation. Calcium hydroxide reacts with carbon dioxide, and the product forms a large number of linear bodies to form flocs. The average particle size of the flocs increases with the increase of the concentration of the linear bodies. In order to obtain a linear body with a higher concentration, a large number of nucleations are required at the initial stage of the reaction, that is, a large number of calcium ions are distributed in the liquid phase. The solubility of calcium hydroxide increases with decreasing temperature, and the solubility of carbon dioxide also increases with decreasing temperature, which provides a basis for carbonization to form nano calcium carbonate with high specific surface area. In addition, Jones et al. (1992) studied the effect of liquid mixing rate on the average crystal size during the precipitation of calcium carbonate in lime water solution. They observed that the average crystal size increased with the increase of stirring rate. Therefore, low temperature and high rotation speed are the key control methods for the large-scale nucleation of nano calcium carbonate to form a high specific surface area. However, as the specific surface area increases, the imbalance of the surface potential of the linear body attracts the calcium carbonate precursor to crystallize and nucleate at the kinked parts of the particle surface, making the linear body coarser. In order to inhibit the recrystallization of the precursor and the nucleation phase, reducing the concentration of calcium ions around the linear body is an effective way to reduce the nucleation of the precursor.

[0012] Chinese patent CN 202311842483 discloses a method for preparing high-purity micron calcium carbonate from calcium-rich tailings, using NH4Cl as a leaching agent to dissolve calcium in the tailings, capture and seal CO2, and form micron-sized calcium carbonate. This method realizes the utilization of tailings, but the calcium carbonate sealing process will inevitably produce chlorides, and the purity is difficult to guarantee.

[0013] Chinese Patent CN202010644465 A method for preparing nano calcium carbonate for water-based coatings, using fructose and galactose as crystal control agents to prepare nano calcium carbonate, using calcium stearate and ammonia water to control the morphology, and adding polyhydroxy fatty acid amide and sodium hexadecylbenzene sulfonate to modify the surface of nano calcium carbonate, carbonizing at up to 95°C, with a specific surface area of ​​up to 110m 2 / g, which needs to be discussed. In addition, too many additives will result in relatively low purity.

[0014] Chinese patent CN202311590354 discloses a method for preparing high-purity nano calcium carbonate, which comprises mixing carbide slag or steel slag with an ammonium chloride solution, leaching, and then solid-liquid separation to obtain a leachate; adjusting the pH of the leachate with ammonia water and adding sulfate, chloride, citric acid, etc. to perform a carbonization reaction, and then performing surface modification to obtain high-purity nano calcium carbonate. Theoretically, the purity of this method will not be very high, the carbonization reaction temperature is 20-35°C, and the specific surface area will not be very high.

[0015] Chinese patent CN201710739711 discloses a method for preparing high-purity calcium carbonate, wherein the ore is ground into 200-mesh powder, placed in an ammonium salt solution for leaching, and the generated carbon dioxide and ammonia are absorbed with water to obtain a mixed solution of ammonium bicarbonate and ammonia water and a calcium salt solution, and the calcium salt solution is reacted with the mixed solution of ammonium bicarbonate and ammonia water to obtain a high-purity calcium carbonate product. The carbonate used in this method is derived from the ore, and the yield is low. The ammonium salt is difficult to absorb and utilize due to its decomposition at high temperature, and is difficult to industrialize.

[0016] Chinese patent CN202211009977 discloses a method for preparing high-purity calcium carbonate, which uses magnesium-containing carbonate minerals as raw materials, leaches out high-purity calcium chloride, and synthesizes high-purity magnesium carbonate trihydrate crystals with the magnesium element in the magnesium-containing carbonate minerals, and then uses element replacement reaction to synthesize high-purity calcium carbonate products. This method converts calcium into chloride, and the subsequent residual chlorine element will affect the purity of calcium carbonate. The chlorine element is removed after multiple washings, and the method is relatively cumbersome.

[0017] Chinese patent CN202310770474 discloses a method for preparing high-purity calcium carbonate using phosphogypsum. The phosphogypsum powder is washed with water and then reacted with ammonium bicarbonate solution to obtain ammonium sulfate mother liquor and calcium-containing solids. The calcium-containing solids react with hydrochloric acid to obtain pure calcium chloride solution. The pure calcium chloride solution reacts with an ammonium carbonate solution formed by passing carbon dioxide and ammonia water to form high-purity calcium carbonate. The method has complicated steps and many by-products make it difficult to control the crystal form.

[0018] Chinese patent CN202310421145 discloses a method for preparing high-purity calcium carbonate using oyster shells as raw materials, wherein oyster shells are used as raw materials to make powder, butyric acid is added to form calcium butyrate, and sodium carbonate is added to form a precipitate, which is high-purity calcium carbonate. The byproduct sodium butyrate in this method will remain in the solution or be doped and attached to the intercrystalline or surface of calcium carbonate, making it difficult to remove.

[0019] Chinese patent CN202311098409 discloses a high-purity nano calcium carbonate and its preparation method. The method uses limestone as raw material, uses a bubbling carbonization method to prepare nano calcium carbonate, and controls crystallization to form nano calcium carbonate by adding a crystal form control agent (an alcohol solution of sulfuric acid-modified starch). In the method, sulfate itself reacts with calcium ions to form a precipitate, which is difficult to separate from calcium carbonate, and the purity cannot be well guaranteed.

[0020] Chinese patent CN201910886510 discloses a method for preparing high-purity calcite-type calcium carbonate. The method uses a high-concentration sodium bicarbonate solution, a calcium chloride solution, and a low-concentration scale inhibitor solution as mother liquors, and uses a constant potential instrument to perform cathode polarization on a stainless steel sheet, so that a scale-forming substance is deposited at the cathode. The scale-forming substance is calcite-type calcium carbonate. The method has a simple process, high requirements on equipment, and the deposited stainless steel sheet is difficult to remove, so it is not suitable for industrialization.

[0021] Chinese patent CN201810459389 discloses a process for preparing high-purity calcium carbonate, wherein calcium oxide is mixed with water, digested and refined, and then allowed to stand for 36-72 hours, a mixture of barium chloride and malic acid is added as a crystal form control agent, and a carbonization reaction is carried out in a carbonization tower, and high-purity calcium carbonate is obtained after drying. This method introduces barium, which can form barium carbonate precipitation with hydrochloric acid, and the purity is difficult to guarantee.

[0022] Chinese patent CN202010360050 discloses a method for preparing high-purity calcium carbonate, wherein limestone is calcined at 200-500°C for 240-360 minutes to obtain quicklime, and after digestion, a slaked lime suspension is obtained, and then nitrogen and carbon dioxide are introduced into the suspension for carbonization reaction.

[0023] Add 1% to 2% phosphate by mass of lime suspension, modify the surface with sodium stearate after carbonization, filter, dry and crush to obtain high-purity calcium carbonate. As we all know, the decomposition temperature of limestone must be at least 750°C to start decomposition. The maximum calcination temperature of this method is only 500°C, and its authenticity needs to be discussed.

[0024] Chinese patent CN202010347299 is a method for preparing high-purity and high-activity nano calcium carbonate, which uses quicklime with high calcium oxide content and few impurities to react with water, uses DTPA to complex metal ions and filter to remove slag to obtain high-purity calcium hydroxide, uses melamine and folic acid to prepare a gel system in proportion as a crystallization medium for calcium carbonate, and adds carbon dioxide to carbonize under the action of stearate to obtain vaterite nano calcium carbonate, and subsequently adds starch to improve the dispersibility of calcium carbonate particles. This method uses DTPA, melamine, folic acid, sodium stearate, starch, etc. These substances are not good for the purity of calcium carbonate, and melamine and DTPA have certain toxicity.

[0025] Chinese patent CN202011249055 A method for preparing high-purity nano calcium carbonate, adding calcium hydroxide to ethyl cellulose and methyl cellulose to obtain a mixed powder, adding the mixed powder to anhydrous ethanol and stirring evenly to form a viscous slurry, and evenly spraying and drying to obtain a mixed film. The mixed film is slowly placed in distilled water containing carbon dioxide until the film forms a porous structure and the precipitation is completely settled, and the precipitate is filtered to obtain the precipitate; after the film is taken out, it is added to the filtrate and stirred, and then 3 times the mass of ethanol aqueous solution is connected to obtain a mixed cellulose solution, and ethanol, distilled water and mixed cellulose are recovered by gradient heating. The precipitate is soaked in low-temperature ultrasound of ethanol aqueous solution, filtered and dried to obtain nano calcium carbonate. This method has cumbersome process steps, high cost, difficult industrialization, and difficult to guarantee dispersibility.

[0026] In summary, there are few studies on purity, specific surface area and dispersibility, and most inventions contain additives, which have a great influence on the purity of nano calcium carbonate, making it difficult to completely separate magnesium from calcium or introducing anions that are more difficult to remove during separation. In order to overcome the fact that nano calcium carbonate contains magnesium of the same family as calcium, make the nano calcium carbonate purer, and overcome the characteristic that nano calcium carbonate is easy to agglomerate when having a high specific surface area, the present invention provides a method for preparing nano calcium carbonate with high specific surface area, high dispersion and high purity, which is different from the prior art. Summary of the invention

[0027] The present invention aims at the situation that the nano calcium carbonate prepared by the above method has low specific surface area, poor dispersibility and frequent use of additives, and provides a high specific surface area, high dispersibility, high purity nano calcium carbonate and its preparation method. The ore is calcined into lime, and after the limestone is digested in water, ammonium salt or ammonia water that is easily decomposed by heat is added, and the aging is allowed to stand for more than 24 hours, which promotes the dissolution of magnesium and is also conducive to the dissolution of magnesium into the liquid phase during overcarbonization. The lime slurry that is aged and allowed to stand is removed from the excess upper layer of water to prepare a concentrated lime slurry with higher purity. The lime slurry is placed in a carbonization tower for carbonization, and water is gradually added to dilute it during carbonization. The linear body of the nano calcium carbonate carbonization process is diluted, which promotes its surface dissolution, inhibits recrystallization, and improves the specific surface area and dispersibility of the nano calcium carbonate. At the end of carbonization, when the calcium hydroxide reaction is complete, carbon dioxide is continuously introduced to achieve overcarbonization, which promotes the dissolution of magnesium into the liquid phase, and finally obtains a nano calcium carbonate suspension. After the suspension is allowed to settle, the excess magnesium-containing liquid phase in the upper layer is removed, and the remaining suspension is a high specific surface area, high dispersion, and high purity nano calcium carbonate suspension. In order to realize the filling application of nano calcium carbonate, surface treatment can be performed at the high purity suspension stage to obtain modified high specific surface area, high dispersion, and high purity active nano calcium carbonate. The suspension can also be directly subjected to filter pressing, drying, and crushing to obtain a high specific surface area, high dispersion, and high purity nano calcium carbonate powder. The obtained nano calcium carbonate has a high specific surface area, good dispersibility, and high purity. It has a high filling value in rubber, adhesives, and special plastics. Its high purity characteristics have good application prospects in reagents, medicines, cosmetics, etc.

[0028] To achieve the above object, the present invention adopts the following technical solution:

[0029] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0030] S1: After limestone is calcined, lime and water are digested in proportion and sand and gravel are removed by sieving;

[0031] S2: adding a certain amount of thermally decomposable ammonium salt or ammonia water to the lime slurry obtained in step S1, and adjusting the solid content to a suitable value;

[0032] S3: After standing for a suitable time, the lime slurry is separated into layers, the upper layer of clear water is removed, and the solid content is concentrated to obtain concentrated lime slurry;

[0033] S4: placing the concentrated lime slurry obtained in step S3 into a carbonization tower, controlling the temperature, stirring rate, carbon dioxide concentration, and carbon dioxide flow rate, and introducing carbon dioxide into the lime slurry, and at the same time, pumping water into the lime slurry;

[0034] S5: When the carbonization pH reaches a suitable value, overcarbonization is achieved, and aeration is stopped to obtain a nano calcium carbonate suspension;

[0035] S6: allowing the suspension obtained in step S5 to settle and removing the upper layer of water to adjust the solid content to a certain range;

[0036] S7: Calculate the amount of stearic acid based on the solid content and add it to the suspension for surface modification. The modified suspension is filtered, dried, crushed and sieved to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0037] Preferably, the ratio of limestone to water in step S1 is 1:4-7.

[0038] Preferably, the ammonium salt used in step S2 includes ammonium carbonate, ammonium bicarbonate, and the ammonium salt or ammonia water is used alone or in combination, with an amount of 1-5% relative to calcium hydroxide.

[0039] Preferably, the amount of concentrated lime slurry used in step S4 is 8-10 kg.

[0040] Preferably, in step S4, the temperature is controlled at 16-20°C, the stirring rate is 800-1500r / min, the carbon dioxide concentration is 30-35%, and the carbon dioxide flow rate is 1.8-3.0m 3 / h.

[0041] Preferably, during the carbonization in step S4, 16-20 kg of water is pumped in at a pumping rate of 400-500 ml / min.

[0042] Preferably, after removing the upper layer of water in step S6, the solid content is 8-12%.

[0043] Preferably, the amount of stearic acid used in step S7 is 2.5-3.0%.

[0044] Preferably, in step S7, the surface modification temperature is 60-70° C., and the surface modification time is 30-60 min.

[0045] The preparation principle of the present invention is as follows:

[0046] The detailed steps of the fine process for efficiently preparing nano calcium carbonate with high specific surface area, high dispersibility and high purity of the present invention, the synergy between raw materials and the importance of process parameter optimization are as follows:

[0047] S1: Calcination and digestion of limestone

[0048] First, high-quality limestone is selected as the starting material and decomposed into calcium oxide (quicklime) by high-temperature calcination. Subsequently, the quicklime obtained is mixed with water in a ratio (1:4 to 1:7) for digestion reaction to generate calcium hydroxide (slaked lime) slurry. In this process, the use of a 200-mesh sieve effectively removes impurities and gravel to ensure the purity of the raw materials. The selection of the ratio of water to lime is crucial, as it directly affects the concentration and uniformity of calcium hydroxide in subsequent steps, and thus affects the purity and dispersibility of the final product.

[0049] S2: Addition of ammonium salt or ammonia water

[0050] In the digested lime slurry, ammonium salts (such as ammonium carbonate, ammonium bicarbonate) or ammonia water that are easily decomposed by heat are quantitatively added. These additives can not only promote the leaching of magnesium ions and increase the dissolution rate of magnesium, but also contribute to the uniform nucleation of calcium carbonate in the subsequent carbonization process. The amount of ammonium salt or ammonia water is 1-5% relative to calcium hydroxide, and it is used alone or in combination. Accurately controlling this ratio is crucial to balancing the removal of magnesium and the nucleation rate of calcium carbonate, which directly affects the purity and specific surface area of ​​the product.

[0051] S3: Concentration and stratification

[0052] The lime slurry containing ammonium salt or ammonia water is left to stand for 24 hours, and the slurry is naturally separated by gravity. After this step, the upper layer of clear water is removed and the solid content is concentrated to 15%. The amount of concentrated lime slurry used in this process is 8-10kg, and the temperature is controlled at 16-20℃ to ensure the stability of calcium hydroxide and promote the release of impurity elements into the liquid phase after dissolution for easy removal. The accuracy of concentration and temperature control has a decisive influence on the nucleation efficiency and the growth morphology of calcium carbonate crystals in the subsequent carbonization process.

[0053] S4: Carbonization process

[0054] The concentrated lime slurry is sent to the carbonization tower, and the temperature, stirring rate (800-1500r / min), carbon dioxide concentration (30-35%) and flow rate (1.8-3.0m 3 / h), and 16-20kg of water is pumped in at a rate of 400-500ml / min to adjust the carbonization rate. The precise control of this series of parameters is aimed at creating an environment conducive to large-scale uniform nucleation, increasing the specific surface area, and at the same time, by continuously diluting the solid content, inhibiting the recrystallization of calcium carbonate crystals, and promoting the effective separation of linear bodies, thereby obtaining highly dispersed nano calcium carbonate.

[0055] S5: Carbonization and suspension preparation

[0056] When the carbonization pH value drops below 6.5, it indicates that the product has been over-carbonized. At this time, the introduction of carbon dioxide is stopped to obtain a nano-calcium carbonate suspension. The over-carbonization step further promotes the dissolution and removal of magnesium ions, thereby improving the purity of the product.

[0057] S6: Sedimentation and solid content adjustment

[0058] After the suspension is allowed to settle and the upper layer of water is removed, the solid content is adjusted to 8-12%. This step is crucial for subsequent surface modification because it directly affects the adsorption efficiency of stearic acid and the dispersion properties of the final product.

[0059] S7: Surface modification and drying

[0060] The amount of stearic acid (2.5-3.0%) is calculated according to the solid content, and the surface modification is carried out at 60-70°C for 30-60 minutes. The addition of stearic acid effectively improves the surface properties of nano calcium carbonate particles and enhances their dispersibility and stability. The modified suspension is filtered, dried, crushed and sieved to finally obtain nano calcium carbonate powder with high specific surface area, high dispersibility and high purity.

[0061] Importance of raw material synergy and process parameter optimization:

[0062] The leaching rate of ammonium salts is used to promote the dissolution of magnesium. After digestion, ammonium salts that are easily decomposed by heat are added to promote the entry of magnesium into the liquid phase, making it easier to remove magnesium. In the carbonization stage, low temperature and high stirring rate are used to promote the dissolution of calcium hydroxide, forming more nucleation sites in the liquid phase, increasing the specific surface area. At the same time, the solid content is continuously diluted to reduce the calcium ion concentration near the new nucleus of calcium carbonate crystallization, inhibiting recrystallization while promoting the separation of linear bodies. At the end of carbonization, over-carbonization is used to further promote the entry of magnesium ions into the liquid phase, and the upper layer of water is removed by sedimentation, so that magnesium is further removed and the purity is improved. The residual ammonium salt is decomposed by heat in the drying stage to form ammonia and carbon dioxide, which further improves the purity.

[0063] During the entire preparation process, the synergistic effect between the raw materials is reflected in the following aspects: ammonium salts or ammonia water promote the dissolution of magnesium, the low temperature and high stirring rate during the carbonization process promotes the dissolution and uniform nucleation of calcium hydroxide, and the overcarbonization and sedimentation steps further purify the product. The precise selection of process parameters not only determines the physical properties of the product (such as specific surface area and dispersibility), but also directly affects the production cost and efficiency. For example, the optimization of temperature, stirring rate, carbon dioxide concentration and flow rate during the carbonization process can significantly improve the nucleation efficiency and reduce unnecessary energy consumption and resource waste.

[0064] Compared with the prior art, the present invention has many significant advantages, which are not only reflected in production efficiency and economic cost, but also in the overall improvement of its scientific research depth and application breadth, which are specifically reflected in the following aspects:

[0065] 1. Raw material cost advantage and economic and environmental protection characteristics: The core of the present invention lies in the selection of low-cost raw materials. This choice not only greatly reduces the production cost, but also actively responds to the current society's urgent need for green and environmentally friendly production. Through a carefully designed production process, the control steps are simplified, and there is no need for complex and expensive equipment or cumbersome operating procedures, thereby achieving efficient utilization of resources. It is particularly worth mentioning that the significant reduction in carbonization time directly improves production efficiency, making the entire production process more efficient and faster. This low-cost, high-efficiency production model has laid a solid foundation for industrial operations, promoted the rapid promotion and application of technology, and is of great significance for promoting the sustainable development of related industries.

[0066] 2. In-depth study of the carbonization process and subsequent treatment: The present invention not only stays at the simple production level, but also conducts in-depth and detailed research on the carbonization process, especially in the dissolution and crystallization of calcium and magnesium ions during the carbonization process. This study not only reveals the essential laws of the carbonization reaction, but also provides a solid theoretical basis and experimental basis for the innovative production technology of bubbling carbonization. Through the precise control of the carbonization conditions, the present invention can effectively control the microstructure and performance of the product, laying a scientific foundation for further optimizing the production process and improving product quality.

[0067] 3. Preparation and application of high-performance nano-calcium carbonate: The nano-calcium carbonate prepared by the present invention not only has high specific surface area, high dispersibility and high purity, but also has uniform morphology and excellent dispersibility. These characteristics make it have extremely high application value in many fields. In the rubber industry, as an efficient filler, it can significantly improve the strength and wear resistance of rubber products; in the field of adhesives and special plastics, it can effectively improve the mechanical properties and processing properties of materials; more importantly, due to its high purity, nano-calcium carbonate also shows broad application prospects in high-end application fields such as reagents, medicines and cosmetics. For example, in the field of medicine, it can be used as a drug carrier or stabilizer to improve the bioavailability and stability of drugs; in cosmetics, it can be used to enhance the fineness and glossiness of products to meet consumers' demand for high-quality cosmetics.

[0068] 4. Through the carefully designed raw material ratio, precisely controlled process parameters and the synergistic effect between the various steps, the present invention successfully achieves the efficient preparation of high specific surface area, high dispersibility and high purity nano calcium carbonate, demonstrates unexpected technical effects, and provides important technological innovations in the field of nano materials.

[0069] 5. The present invention not only achieves significant improvements in cost control and production efficiency, but also demonstrates significant technological progress in scientific research depth and product application breadth, opening up a new path for the preparation and application of nano-calcium carbonate, and has a far-reaching driving effect on the transformation, upgrading and high-quality development of related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 The conductivity, pH, and Ca in the carbonization process of Example 1 are 2+ Mg 2+ Trend graph with carbonization time.

[0071] Figure 2-3 This is a scanning electron microscope image of high specific surface area, high dispersion, and high purity nano calcium carbonate prepared in Example 1.

[0072] Figure 4-5 This is a scanning electron microscope image of high specific surface area, high dispersion, and high purity nano calcium carbonate prepared in Example 2.

[0073] Figure 6 This is a scanning electron microscope image of high specific surface area, high dispersion, and high purity nano calcium carbonate prepared in Example 3.

[0074] Figure 7 This is a scanning electron microscope image of high specific surface area, high dispersion, and high purity nano calcium carbonate prepared in Example 4.

[0075] Figure 8-9 This is a scanning electron microscope image of high specific surface area, high dispersion, and high purity nano calcium carbonate prepared in Example 5.

[0076] Figure 10-11 This is a scanning electron microscope image of ordinary nano calcium carbonate prepared in Comparative Example 1.

[0077] Figure 12-13 This is a scanning electron microscope image of ordinary nano calcium carbonate prepared in Comparative Example 2.

[0078] Figure 14-15 This is a scanning electron microscope image of ordinary nano calcium carbonate prepared in Comparative Example 3. DETAILED DESCRIPTION

[0079] In order to better present the present invention, it is illustrated through specific implementation cases, which belong to the protection scope of the present invention but do not limit the protection scope of the present invention.

[0080] Example 1

[0081] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0082] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:4 and the sand and gravel are removed through a 200 mesh sieve.

[0083] S2: Add 3% of ammonium carbonate relative to calcium hydroxide to the lime slurry obtained in step S1, and adjust the solid content to 5%.

[0084] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0085] S4: Put 8 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 18°C, stirring rate at 1500 r / min, carbon dioxide concentration at 35%, and carbon dioxide flow rate at 3.0 m 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 20kg of water is pumped into the lime slurry at 420ml / min.

[0086] S5: When the carbonization pH reaches 6.5, that is, overcarbonization is achieved, aeration is stopped, and a nano-calcium carbonate suspension is obtained.

[0087] S6: The suspension obtained in step S5 is allowed to settle, and the upper layer of water is removed to adjust the solid content to 8%.

[0088] S7: Calculate the amount of stearic acid to be 2.5% based on the solid content, heat the suspension to 70°C for surface modification for 30 minutes, filter the modified suspension, dry, crush and sieve to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0089] Example 2

[0090] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0091] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:7 and the sand and gravel are removed through a 200 mesh sieve.

[0092] S2: Add 2% ammonia water, 2% ammonium bicarbonate and 1% ammonium carbonate (total 5%) relative to calcium hydroxide to the lime slurry obtained in step S1, and adjust the solid content to 5%.

[0093] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0094] S4: Put 10 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 16°C, stirring rate at 1200 r / min, carbon dioxide concentration at 35%, and carbon dioxide flow rate at 1.8 m 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 16kg of water is pumped into the lime slurry at 500ml / min.

[0095] S5: When the carbonization pH reaches 6.5, that is, overcarbonization is achieved, aeration is stopped, and a nano-calcium carbonate suspension is obtained.

[0096] S6: The suspension obtained in step S5 is allowed to settle, and the upper layer of water is removed to adjust the solid content to 12%.

[0097] S7: Calculate the amount of stearic acid to be 2.5% based on the solid content, heat the suspension to 60°C for surface modification for 30 minutes, filter the modified suspension, dry, crush and sieve to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0098] Example 3

[0099] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0100] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:5.5 and the sand and gravel are removed through a 200 mesh sieve.

[0101] S2: Add 1% of ammonium bicarbonate relative to calcium hydroxide to the lime slurry obtained in step S1, and adjust the solid content to 5%.

[0102] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0103] S4: Put 10 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 20°C, stirring rate at 800 r / min, carbon dioxide concentration at 30%, and carbon dioxide flow rate at 3 m / s. 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 20kg of water is pumped into the lime slurry at 400ml / min.

[0104] S5: When the carbonization pH reaches 6.5, that is, overcarbonization is achieved, aeration is stopped, and a nano-calcium carbonate suspension is obtained.

[0105] S6: The suspension obtained in step S5 is allowed to settle, and the upper layer of water is removed to adjust the solid content to 10%.

[0106] S7: Calculate the amount of stearic acid to be 3.0% based on the solid content, heat the suspension to 60°C for surface modification for 30 minutes, filter the modified suspension, dry, crush and sieve to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0107] Example 4

[0108] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0109] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:6 and the sand and gravel are removed through a 200 mesh sieve.

[0110] S2: Add 3% ammonia water relative to calcium hydroxide to the lime slurry obtained in step S1, and adjust the solid content to 5%.

[0111] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0112] S4: Put 8 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 16°C, stirring rate at 1000 r / min, carbon dioxide concentration at 33%, and carbon dioxide flow rate at 2.2 m 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 18kg of water is pumped into the lime slurry at 450ml / min.

[0113] S5: When the carbonization pH reaches 6.5, that is, overcarbonization is achieved, aeration is stopped, and a nano-calcium carbonate suspension is obtained.

[0114] S6: The suspension obtained in step S5 is allowed to settle, and the upper layer of water is removed to adjust the solid content to 12%.

[0115] S7: The amount of stearic acid is calculated to be 2.8% based on the solid content. The suspension is heated to 60°C for surface modification for 30 minutes. The modified suspension is filtered, dried, crushed and sieved to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0116] Example 5

[0117] A method for preparing high specific surface area, high dispersion and high purity nano calcium carbonate comprises the following steps:

[0118] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:5 and the sand and gravel are removed through a 200 mesh sieve.

[0119] S2: Add 2% ammonia water and 2% ammonium carbonate relative to calcium hydroxide to the lime slurry obtained in step S1, and adjust the solid content to 5%.

[0120] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0121] S4: Put 10 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 20°C, stirring rate at 1200 r / min, carbon dioxide concentration at 31%, and carbon dioxide flow rate at 2.5 m / s. 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 20kg of water is pumped into the lime slurry at 500ml / min.

[0122] S5: When the carbonization pH reaches 6.5, that is, overcarbonization is achieved, aeration is stopped, and a nano-calcium carbonate suspension is obtained.

[0123] S6: The suspension obtained in step S5 is allowed to settle, and the upper layer of water is removed to adjust the solid content to 10%.

[0124] S7: Calculate the amount of stearic acid to be 3.0% based on the solid content, heat the suspension to 65°C for surface modification for 30 minutes, filter the modified suspension, dry, crush and sieve to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

[0125] Comparative Example 1

[0126] A method for preparing common nano calcium carbonate comprises the following steps:

[0127] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:6 and the sand and gravel are removed through a 200 mesh sieve.

[0128] S2: The solid content of the lime slurry obtained in step S1 is adjusted to 5%.

[0129] S3: After standing for 24 hours, the lime slurry is separated into layers, the upper layer of water is removed, and the solid content is concentrated to obtain a concentrated lime slurry with a solid content of 15%.

[0130] S4: Put 15 kg of concentrated lime slurry obtained in step S3 into a carbonization tower, and control the temperature at 23°C, stirring rate at 1000 r / min, carbon dioxide concentration at 31%, and carbon dioxide flow rate at 2.5 m / s. 3 / h, pass carbon dioxide into the lime slurry.

[0131] S5: When the carbonization pH reaches 7, aeration is stopped to obtain a common nano calcium carbonate suspension.

[0132] S6: Calculate the amount of stearic acid to be 2.5% based on the solid content, heat the suspension to 70°C for surface modification for 30 minutes, filter the modified suspension, dry, crush and sieve to obtain ordinary nano calcium carbonate powder.

[0133] Comparative Example 2

[0134] A method for preparing nano calcium carbonate with high specific surface area comprises the following steps:

[0135] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:4 and the sand and gravel are removed through a 200 mesh sieve.

[0136] S2: The solid content of the lime slurry obtained in step S1 is adjusted to 15%.

[0137] S3: Put 10 kg of lime slurry obtained in S2 into the carbonization tower, control the temperature at 18 °C, stirring rate at 1500 r / min, carbon dioxide concentration at 33%, and carbon dioxide flow rate at 3.0 m 3 / h, carbon dioxide is introduced into the lime slurry, and at the same time, 20kg of water is pumped into the lime slurry at 500ml / min.

[0138] S4: When the carbonization pH reaches 6.5, aeration is stopped to obtain a nano-calcium carbonate suspension.

[0139] S5: The suspension obtained in S4 is allowed to settle and the upper layer of water is removed to adjust the solid content to 10%.

[0140] S6: The amount of stearic acid is calculated to be 2.5% based on the solid content, the suspension is heated to 65°C for surface modification for 30 minutes, the modified suspension is filtered, dried, crushed and sieved to obtain nano calcium carbonate powder with high specific surface area.

[0141] Comparative Example 3

[0142] A method for preparing common low-specific surface area nano calcium carbonate comprises the following steps:

[0143] S1: After the limestone is calcined, the lime and water are digested in a ratio of 1:7 and the sand and gravel are removed through a 200 mesh sieve.

[0144] S2: The solid content of the lime slurry obtained in step S1 is adjusted to 15%.

[0145] S3: Put 8 kg of lime slurry obtained in S2 into the carbonization tower, control the temperature at 22°C, stirring rate at 1000 r / min, carbon dioxide concentration at 28%, and carbon dioxide flow rate at 1.8 m 3 / h.

[0146] S4: When the carbonization pH reaches 7, aeration is stopped to obtain a nano-calcium carbonate suspension.

[0147] S5: The amount of stearic acid is calculated to be 2.8% based on the solid content. The suspension is heated to 65°C for surface modification for 30 minutes. The modified suspension is filtered, dried, crushed and sieved to obtain ordinary low specific surface area nano calcium carbonate powder.

[0148] The calcium carbonate powders prepared in Examples 1-5 and Comparative Examples 1-3 were examined by electron scanning microscopy (SEM). Figure 2-15 shown.

[0149] Depend on Figure 2-15It can be seen that in Examples 1-5, due to the careful addition of the key step of ammonium salt or ammonia water, the dispersion performance of the entire reaction system is significantly improved. This improvement is not accidental, but is based on a deep scientific principle: ammonium salt or ammonia water can react effectively with magnesium ions in water, prompting magnesium ions to change from a solid phase state to a liquid phase state that is more soluble in water. Through this conversion, magnesium ions that may originally exist in a solid form and hinder the uniform dispersion of particles are effectively dissolved and dispersed in the liquid phase, thereby greatly reducing the occurrence of agglomeration.

[0150] Furthermore, in the embodiment, a low temperature carbonization technique is used. The choice of this step is very strategic, because the low temperature condition not only helps to maintain the structural stability of the material, but also effectively controls the growth rate of the particles during the carbonization process, thereby obtaining a product with a smaller particle size and uniform distribution. The use of low temperature carbonization technology complements the aforementioned ammonium salt or ammonia water treatment, and together promotes the realization of excellent dispersibility of the final product.

[0151] In contrast, the situation in the comparative example is quite different. Since no ammonium salt is used to promote the dissolution of magnesium ions, magnesium ions still exist in large quantities in the solid phase, which not only increases the interaction between particles, but also makes it difficult for magnesium ions to enter the liquid phase through the subsequent carbonization process and be removed with water. Therefore, the product in the comparative example presents a clear chain and cluster structure, which not only affects the dispersibility of the product, but may also have an adverse effect on its performance, such as reducing the reaction activity and increasing the difficulty of processing.

[0152] In summary, in Examples 1-5, by adding ammonium salt or ammonia water to promote the dissolution of magnesium ions, and combining low-temperature carbonization technology, the product dispersibility was significantly improved and the particle size was effectively controlled. However, the comparative example lacked these key steps, resulting in a poor product structure, which brought many challenges to subsequent applications. This comparison not only highlights the importance of scientific methods in material preparation, but also provides useful inspiration for research in related fields.

[0153] According to GB / T 19281-2014, the purity (before surface modification) and specific surface area of ​​the nano calcium carbonate prepared in Examples 1-5 and Comparative Examples 1-3 were measured using a titration method and a static specific surface area tester. The results are shown in the following table:

[0154]

[0155] It can be seen from the above table that the purity and specific surface area of ​​the nano calcium carbonate prepared in Examples 1-5 are significantly higher than those of the nano calcium carbonate prepared in Comparative Examples 1-3, indicating that the technology of the present invention has significant progress.

[0156] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate, characterized in that: The following steps are involved: S1: After limestone is calcined, lime and water are digested in proportion and sand and gravel are removed by sieving; S2: adding a certain amount of thermally decomposable ammonium salt or ammonia water to the lime slurry obtained in step S1, and adjusting the solid content to a suitable value; S3: After standing for a suitable time, the lime slurry is separated into layers, the upper layer of clear water is removed, and the solid content is concentrated to obtain concentrated lime slurry; S4: placing the concentrated lime slurry obtained in step S3 into a carbonization tower, controlling the temperature, stirring rate, carbon dioxide concentration, and carbon dioxide flow rate, and introducing carbon dioxide into the lime slurry, and at the same time, pumping water into the lime slurry; S5: When the carbonization pH reaches a suitable value, overcarbonization is achieved, and aeration is stopped to obtain a nano calcium carbonate suspension; S6: allowing the suspension obtained in step S5 to settle and removing the upper layer of water to adjust the solid content to a certain range; S7: Calculate the amount of stearic acid based on the solid content and add it to the suspension for surface modification. The modified suspension is filtered, dried, crushed and sieved to obtain high specific surface area, high dispersion and high purity nano calcium carbonate powder.

2. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: The ratio of limestone to water in step S1 is 1:4-7.

3. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: The ammonium salt used in step S2 includes ammonium carbonate, ammonium bicarbonate, and the ammonium salt or ammonia water is used alone or in combination, with an amount of 1-5% relative to calcium hydroxide.

4. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: The amount of concentrated lime slurry used in step S4 is 8-10 kg.

5. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: In step S4, the temperature is controlled at 16-20°C, the stirring rate is 800-1500r / min, the carbon dioxide concentration is 30-35%, and the carbon dioxide flow rate is 1.8-3.0m 3 / h.

6. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: During the carbonization in step S4, 16-20 kg of water is pumped in at a pumping rate of 400-500 ml / min.

7. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: After removing the upper layer of water in step S6, the solid content is 8-12%.

8. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: In step S7, the amount of stearic acid used is 2.5-3.0%.

9. The method for preparing high specific surface area, high dispersion, high purity nano calcium carbonate according to claim 1, characterized in that: In step S7, the surface modification temperature is 60-70° C., and the surface modification time is 30-60 min.

10. A high specific surface area, high dispersion, high purity nano calcium carbonate prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing high-purity calcium carbonate

    CN107285362A

  • A preparation process for high-purity calcium carbonate

    CN108516571B

  • Preparation method of high-purity calcite type calcium carbonate

    CN110541189A

  • Preparation method of high-purity and high-activity nano calcium carbonate

    CN111453754A

  • Preparation method of high-purity calcium carbonate

    CN111484060A

Cited By

  • Preparation method and application of modified nano calcium carbonate based on biomass ash

    CN122352662A